2021
DOI: 10.1002/mc.23369
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins mitigate bile acid‐induced changes in GSTT2 levels in a panel of racially diverse patient‐derived primary esophageal cell cultures

Abstract: Persistent and symptomatic reflux of gastric and duodenal contents, known as gastroesophageal reflux disease (GERD), is the strongest risk factor for esophageal adenocarcinoma (EAC). Despite similar rates of GERD and other risk factors across racial groups, EAC progression disproportionately impacts Caucasians. We recently reported that elevated tissue levels of the detoxification enzyme GSTT2 in the esophagi of Blacks compared to Caucasians may contribute protection. Herein, we extend our research to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Furthermore, MMP-9 expression is inversely correlated with protein levels of the phase II detoxification glutathione-s-transferase pi (GSTP1), with increased levels of GSTP1 in normal patients and those with esophagitis [ 79 ]. We recently showed that C-PAC increases levels of the phase 2 detoxification enzyme glutathione-s-transferase theta 2 (GSTT2) and protects against acidified bile acid induced cell death in patient-derived primary normal esophageal cells [ 80 ]. Thus, the ability of cranberry constituents to favorably impact esophageal cells, both primary and immortalized cell cultures, across a range of histopathology lends support for the investigation of cranberry constituents in cohorts at increased risk for progression to EAC, such as BE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MMP-9 expression is inversely correlated with protein levels of the phase II detoxification glutathione-s-transferase pi (GSTP1), with increased levels of GSTP1 in normal patients and those with esophagitis [ 79 ]. We recently showed that C-PAC increases levels of the phase 2 detoxification enzyme glutathione-s-transferase theta 2 (GSTT2) and protects against acidified bile acid induced cell death in patient-derived primary normal esophageal cells [ 80 ]. Thus, the ability of cranberry constituents to favorably impact esophageal cells, both primary and immortalized cell cultures, across a range of histopathology lends support for the investigation of cranberry constituents in cohorts at increased risk for progression to EAC, such as BE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond dysbiosis, reflux components are well documented to induce DNA damage in esophageal cells and to stimulate cytokine-mediated inflammation further contributing toward epithelial injury, immune cell migration, genetic instability and cancer progression (21,24). Repeated exposure to refluxate also leads to diminished defense mechanisms as evidenced by esophageal barrier dysfunction and reduced levels of esophageal DNA repair enzymes, inferring compromised repair capacity in reflux-exposed esophageal epithelium (21,25,26). Reflux-induced mucosal damage coupled with esophageal barrier dysfunction allows for increased interaction between pathogenic bacteria and the epithelium further promoting esophageal injury and risk for EAC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has previously shown the cancer inhibitory potential of C-PAC utilizing human esophageal normal, BE, and EAC cell lines and OE19 EAC tumor xenografts ( 22 , 34 36 , 50 ). The current study extends evaluation of C-PAC to a more translationally relevant reflux-induced EAC model.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond dysbiosis, reflux components are well documented to induce DNA damage in esophageal cells and to stimulate cytokine-mediated inflammation, further contributing toward epithelial injury, immune cell migration, genetic instability, and cancer progression ( 18 , 21 ). Repeated exposure to refluxate also leads to diminished defense mechanisms, as evidenced by esophageal barrier dysfunction and reduced levels of esophageal DNA repair enzymes, suggesting compromised repair capacity in reflux-exposed esophageal epithelium ( 18 , 22 , 23 ). Reflux-induced mucosal damage coupled with esophageal barrier dysfunction allows for increased interaction between pathogenic bacteria and epithelium, further promoting esophageal injury and risk for EAC progression.…”
Section: Introductionmentioning
confidence: 99%